Commercial navigation along the Northern Sea Route: Prospects and impacts - Karel van Hussen; Twan de Korte; Rick Janse; Onno de Jong; Marten van den Bossche (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This report assesses the business case for commercial navigation through Arctic waters along the Northern Sea Route and offers insights in the possible impacts on global trade flows.
Keywords: 330